TESTING THE LEARNING OUTCOMES OF WOOD TECHNOLOGY COURSE - Acar, Mehmet; Ziya Erdil, Yusuf; Kasal, Ali; Demirci, Selcuk (Innovation in Woodworking Industry and Engineering design, 2013)
In this study, realization level of learning outcomes is examined within the context of a pilot course. Purpose of this study is to test learning outcomes of the pilot course which are determined by instructor. For this purpose, “Wood Technology” course, which has been taught at Department of Wood Science and Furniture Design and Department of Woodworking Industrial Engineering, is chosen as a pilot course. The course consists of 12 units. Learning outcomes of each unit are prepared by the instructor. To test realization level of learning outcomes, two different questionnaire were prepared and applied to students who had taken the course in the period when study was conducted. One of the questionnaire was to determine „students’ expectation“ from each course unit before teaching. The other questionnaire was to determine „achieved level“ at the end of each course unit. To check the validity of achieved level, a quiz was given at the end of each course unit. In addition, another questionnaire was applied to determine level of „achieved learning outcomes“ of graduated students. All data were analyzed statistically and results were compared by t tests. As a result of statistical analyses, it was determined that students underestimated their learning outcomes by 105 %; i.e.; they learned two times more than their expectation. In general, it can be concluded that determination and testing learning outcomes in a course is necessary in order to achieve a better learning-teaching balance.